A Survey of Standard Protocols for Endodontic Treatment in North of KSA. (4th May 2014) - Iqbal, Azhar; Akbar, Iftikhar; Qureshi, Beenish; Sghaireen, Mohd G.; AL-Omiri, Mahmoud K.
Abstract : The objective of this study was to collect information regarding methods, materials, and attitudes employed during the endodontic treatment by dentists in north of Saudi Arabia. A questionnaire was designed and distributed among 300 dentists in north of Saudi Arabia to collect the data about the standard protocols of endodontic treatment. The collected data was analyzed by using the SPSS 10 computer software. Out of a total of 300 surveyed dentists, the 66% response rate showed that this study was true representation of the endodontic treatment performed by the dentists in north of Saudi Arabia. 152 (76%) were general dentists and 48 (24%) were endodontists. 18 (9%) were using rubber dam as the method of isolation during endodontic treatment. 173 (86.5%) were using only measurement radiographs for working length determination and 27 (13.5%) were using both electronic apex locator and measurement radiographs. 95 (47.5%) of the respondents were using standardized technique and 25 (12.5%) were using step-down as a root canal preparation technique. 127 (63.5%) of the respondents were using lateral condensation technique, with gutta percha points for root canal obturation.